2006
DOI: 10.1074/jbc.m511786200
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120-mediated Apoptosis of T Cells Is Regulated by the Membrane Tyrosine Phosphatase CD45

Abstract: The molecular mechanism of the human immunodeficiency virus type 1 (HIV-1) gp120-induced apoptosis of bystander T cells is not well defined. Here, we demonstrate that CD45, a key component of the T cell receptor pathway, plays a crucial role in apoptosis induced by HIV-1 gp120. We observed that HIV-1 gp120-induced apoptosis was significantly reduced in a CD45-deficient cell line and that reconstitution of CD45 in these cells restored gp120-induced apoptosis. However, expression of a chimeric protein containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…2D), implying that direct cell-to-cell communication between pDCs and mB cells is required for mB cell apoptosis. HIV gp120 contains binding regions for CD4 and the HIV coreceptor and has been shown to induce significant FasL expression via cellular receptors (48). Consistent with this information, gp120 induced more FasL expression in pDCs than HIV (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…2D), implying that direct cell-to-cell communication between pDCs and mB cells is required for mB cell apoptosis. HIV gp120 contains binding regions for CD4 and the HIV coreceptor and has been shown to induce significant FasL expression via cellular receptors (48). Consistent with this information, gp120 induced more FasL expression in pDCs than HIV (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we demonstrate that gp120 binding to either CD4 or CXCR4 each fails to activate Akt in primary human CD4 T cells, similar to the previous reports that gp120 does not activate Akt in cell lines (29,61). Recent studies indicate that the phosphorylation of BH 3 -only proteins by Akt or by p38/JNK results in divergent effects on proapoptotic activity of these proteins.…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, both the extra-cellular domain and the catalytic activity of CD45 were observed to be necessary for GP120-promoted cell death. 81 Molecular analysis of this pathway revealed that GP120 enhances the phosphatase activity of CD45, which translates to the dephosphorylation of Lck. 81 CD45 was also observed to enhance the induction of FasL expression in cells treated with GP120; nonetheless, it did not promote Fas-mediated cell death.…”
Section: Potential Regulation Of Fas Ligand Expression Bymentioning
confidence: 99%
“…81 CD45 was also observed to enhance the induction of FasL expression in cells treated with GP120; nonetheless, it did not promote Fas-mediated cell death. 78,81 Interestingly, CD45 is required for GP120 initiated inactivation of AKT and caspase-3 processing. 81 The impact of other PTPs involved in the regulation of AKT in HIV-infection associated cell death has yet to be investigated.…”
Section: Potential Regulation Of Fas Ligand Expression Bymentioning
confidence: 99%